Religion, caste, and nation in South India Maraimalai Adigal, the Neo-Saivite movement, and Tamil nationalism, 1876-1950 - Vaithees, V. Ravi (New Delhi Oxford University Press, 2015)
Departing sharply from the principal focus on language and the 'secular-modern' in contemporary nationalism studies, this volume examines the religious roots of nationalism, specifically the religious roots of non-Brahmin Tamil nationalism and the Dravidian movement in India. The book argues that it was the anti-Aryan, anti-Sanskritic imperatives and spirit of the neo-Saivite movement that came to inform and animate the neo-Saivite readings of the Tamil and Indian past and indeed the articulation of neo-Saivism as a form of non-Brahmin Tamil nationalism.
Keywords: Electronic books; Religion and politics -- India, South -- History -- 19th century; Religion and politics -- India, South -- History -- 20th century